TOTAL INTRAVENOUS ANESTHESIA (TIVA) VS. INHALATIONAL ANESTHESIA IN SMALL ANIMALS (International Seven Journal of Multidisciplinary, 2025)
Objective: To compare the effects, advantages and disadvantages of total intravenous anesthesia (TIVA) and inhalational anesthesia in small animals, evaluating anesthetic recovery, cardiovascular stability, patient safety, environmental impact and economic viability. General anesthesia is critical in veterinary, with TIVA standing out as a growing option due to precise dose control and lower environmental pollution. On the other hand, inhalational anesthesia is still widely used due to the ease of adjusting the intensity of the anesthetic. This study conducted a literature review of papers published in the last ten years, examining clinical and experimental research that compared these techniques. The findings show that TIVA promotes a more agile and stable anesthetic recovery, particularly in elderly patients or those with liver problems, in addition to reducing environmental hazards. On the other hand, inhalational anesthesia is more recommended for long-term procedures due to the ease of adjustment of anesthesia, even though it is linked to a higher risk of hypotension and respiratory depression. Combined protocols have been adopted to optimize benefits and minimize risks. It is therefore concluded that the choice of technique should consider the patient's clinical status, the type of procedure and the available infrastructure.